Analyzing the Influence of Social Media Influencers on Consumer Purchase Intention: A Case Study of Fashion market in the Nepalese Market - Khadka, Rakshya; Nuangjamnong, Chompu (AU Hybrid International Conference 2024 on " Entrepreneurship & Sustainability in the Digital Era" under the theme of "People Centric Knowledge in Intelligence World", 2024)
Purpose – This study investigates the influence of social media influencers on consumer purchase intention within the Nepalese fashion market, focusing on social media influencers trustworthiness, social media influencers credibility, social media influencers authenticity, and social media influencers expertise as key factors. Design/Methodology/Approach – The research employs a quantitative approach, utilizing a sample size of 390 respondents who completed a structured questionnaire. Multiple linear regression analysis is used to analyze the data and explore the relationships between social media influencer characteristics and consumer purchase intention. Findings – The study reveals that while credibility and expertise significantly impact consumer purchase intention, trustworthiness and authenticity do not. Influencers perceived as credible and knowledgeable about fashion trends are more likely to influence consumer purchasing decisions. Research Limitations/Implications – Limitations include a sample population skewed towards younger, higher-income individuals from the central region of Nepal, as well as the reliance on closed-ended survey questions. Future research should consider a more diverse sample and employ mixed-methods approaches for deeper insights. Originality/value – This study contributes to understanding the nuances of influencer marketing in the Nepalese fashion industry, highlighting the importance of credibility and expertise in driving consumer purchase intention. It offers valuable insights for businesses and marketers seeking to enhance their influencer marketing strategies in Nepal. Keywords – Social Media Influencer Trustworthiness, Social Media Influencer Credibility, Social Media Influencer Authenticity, Social Media Expertise and Consumer Purchase Intention JEL classification code – M31, M37, O33, L81